Everybody matters : a first look at respect for othersl - Thomas ,Pat; Harker , Lesley (London Wayland, 2023)
This book introduces children to the concept of respect. It explains that everyone deserves respect, whether by being treated fairly or by not being discriminated against because they are different. It explains how to earn respect, by being polite, honest and listening to others. It also explains how having respect for ourselves and others makes the world a better place. Notes for parents and teachers at the back of the book provide valuable advice for how to share this book with your child or classss
Education
Keywords: Children's stories; Respect for persons